DISCOURSE MARKER ANALYSIS IN AVENGERS: ENDGAME MOVIE - Ana Nisa Ussolichah; Arindi Indra; Hesti Dwi Rahayu; Atsani Wulansari (Universitas Galuh, 2021)
This study examines the use of Discourse Marker in Avengers: Endgame movie. Discourse Markers are words that connect the speaker with what has been said before. The purpose of discourse markers is to keep the conversation owing and not stiff. This discourse marker can improve a person's speaking ability to make it easier to understand. This research uses analytical methods taken from Avengers: Endgame movie, directed by Anthony Russo and Joe Russo.Avengers: Endgame movie is a 2019 American Superhero movie based on the Marvel Comics superhero team by Avengers. The data collected were analyzed using a qualitative descriptive method: the procedure data collection, data analysis, and presentation of the study results. The results showed (1) the number of discourse markers used in the Avengers: Endgame movie ; (2) the discourse marker that appears the most.